2015
DOI: 10.1371/journal.pone.0131241
|View full text |Cite
|
Sign up to set email alerts
|

Dual Fatty Acid Synthase and HER2 Signaling Blockade Shows Marked Antitumor Activity against Breast Cancer Models Resistant to Anti-HER2 Drugs

Abstract: Blocking the enzyme Fatty Acid Synthase (FASN) leads to apoptosis of HER2-positive breast carcinoma cells. The hypothesis is that blocking FASN, in combination with anti-HER2 signaling agents, would be an effective antitumor strategy in preclinical HER2+ breast cancer models of trastuzumab and lapatinib resistance. We developed and molecularly characterized in vitro HER2+ models of resistance to trastuzumab (SKTR), lapatinib (SKLR) and both (SKLTR). The cellular interactions of combining anti-FASN polyphenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 53 publications
2
44
0
Order By: Relevance
“…We and others have demonstrated that EGCG displays antitumor activity without affecting food intake or weight loss, which are common side effects of other FASN inhibitors (37,38,47). We have previously shown that EGCG produces apoptosis in vitro and in vivo in breast cancer (19,37,38). Here, EGCG showed strong CPI and high apoptosis in vitro and moderate antitumor activity in vivo.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We and others have demonstrated that EGCG displays antitumor activity without affecting food intake or weight loss, which are common side effects of other FASN inhibitors (37,38,47). We have previously shown that EGCG produces apoptosis in vitro and in vivo in breast cancer (19,37,38). Here, EGCG showed strong CPI and high apoptosis in vitro and moderate antitumor activity in vivo.…”
Section: Discussionmentioning
confidence: 65%
“…Same treatments were assessed in monotherapy. Following treatment, cell viability was measured using the standard colorimetric MTT assay as previously described (19). Combinatorial effects were evaluated using the Interaction index (Ix) ¼ P (% CPI drug alone)/% CPI combination.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, nearly all research is dealing with administration of one kind DNA or RNA at a time ("mono transfection"). However, in work such as cell reprogramming (e.g., induced pluripotent stem cells) or the need of multi-expression (e.g., double knock down), requirements of sending two different (or more) DNA or RNA ("dual transfection") are in necessity [5][6][7][8][9]. The conventional manipulation is to dispense a mixture of distinct complexes to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there were also preclinical studies showing that trastuzumab-induced reprogramming of the HER axis resulted in the increase of EGFR and HER3 expression after long-term trastuzumab treatment in cell lines, which may correlate with primary resistance to trastuzumab (48). As mentioned above, trastuzumab resistance in HER2 + BC might be caused by excessive EGFR expression (49,50), making EGFR an effective target to evaluate in response to trastuzumab treatment (51).…”
Section: Does Every Her2 + Bc Patient Benefit From Targeted Therapy?mentioning
confidence: 97%